Engineering risk management in performance-based building environments - Almeida, Nuno Marques; Sousa, Vitor; Dias, Luís Alves; Branco, Fernando (Journal of Civil Engineering and Management, 2015)
Nowadays, a wide range of stakeholders seek explicit performance and risk information on construction projects. These stakeholders include end-users, authorities, insurance companies and financial institutions, among others. They look for proof that engineering risks are being properly managed and that specified performance-based requirements are fulfilled throughout all stages of the project (e.g. technical requirements related to the building such as structural safety, structural serviceability, structural durability, fire safety, energy efficiency, or others). Such demonstration can be conveyed through statements of technical conformity, such as technical risk reports or engineering performance certificates. Statements of conformity are particularly valuable to make informed decisions associated with contractual or other legal warranties against building nonconformities. This paper describes the conceptual background and the methodologies undertaken to design and develop a management framework that enables recognition of the conformity assessment results of building projects. It also presents the outreach of this management framework throughout the planning, programming, design, construction and use phases of building projects. This paper also summarizes the wide range of practical implications and benefits of this management framework for authorities and official bodies, owners and their representatives, banks and insurance companies, conformity assessment bodies, designers, builders, suppliers and end-users.